The impact of capital flows on exchange rates: Evidence from Sub-Saharan Africa - Letsie, Molebogeng (Graduate School of Business (GSB), 2022)
With the low levels of domestic savings, capital flows can narrow the financing gap and contribute to economic growth and development. However, capital flows can also lead to negative, possibly unintended, consequences. As such, the study sought to ascertain the relationship between capital flows and the exchange rate. The objective of this study was to analyse the impact of capital flows on exchange rates, specifically in Sub-Saharan Africa, using the system-generalised method-of-moments (GMM) estimator and panel data of 45 countries from 1990 to 2019. The study is particularly important considering the wave of reforms in the 1980s, advocated for by the International Monetary Fund (IMF), which led to a substantial increase in capital inflows in the region. This study found that a relationship between capital flows and the exchange rate does exist and that capital flows do cause the exchange rate to appreciate when controlling for endogeneity. In addition, the findings of the study also confirmed that while both portfolio flows and foreign direct investment cause the exchange rate to appreciate, the impact of portfolio flows on the exchange rate is much more significant than that of foreign direct investment.